Catalysis for the Conversion of Biomass and its Derivatives. (Max Planck Research Library for the History and Development of Knowledge.) Edited by Malte Behrens and Abhaya K. Datye. Issue 37 (2nd August 2013) - Rose, Marcus
<x xml:space="preserve">Abstract</x> epubli, Berlin, 2013. 476 pp., softcover, € 26.94.—ISBN 978‐3844242829<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>